Statistics of South Delta-Aquariids (SDA) meteor showers registered at UNIVAP in 2017 and 2018 - Rita de Cássia Alves da Silva; Guilherme Jayme Allan Pimentel; Francisco Carlos Rocha Fernandes; Lucas Antonio Caritá; Irapuan Rodrigues (Revista Brasileira de Ensino de Física)
Abstract Meteor showers, seen at regular and frequent intervals, occur when the Earth crosses the orbit of a comet and many small dust particles enter the Earth's atmosphere. In this paper we compare the Southern Delta-Aquariids (SDA) shower recorded by the UVP1 and UVP2 meteor monitoring stations in the Southeastern of Brazil, in 2017 and 2018. These stations are affiliated with EXOSS Citizen Science meteor monitoring network. The SDA meteor shower represented the most active radiant in these two years of data recorded by these stations. 27 detections were achieved in 2017 (between July 12 and August 24) and 15 detections in 2018 (between July 18 and August 20). The meteor properties highlighted and compared throughout the present text are: duration, apparent magnitude and angular velocity. We used estimations provided by the UFOAnalyzer program, since there is no doubled captures from diverse stations far separated. This article helps to highlight the importance of the EXOSS project, aligned with the concept of citizen science, valuing the partnership between amateur astronomers and professional scientists in data collection and wide dissemination of knowledge related to the science of meteors. This work is the result of two scientific initiation projects, with an educational cooperation between the Universidade do Vale do Paraíba (UNIVAP) and the Instituto Federal de Educação, Ciência e Tecnologia de São Paulo campus São José dos Campos (IFSP-SJC).